Challenges of Social Management in the Comprehensive Community Health Area (ASIC). - RINCÓN MAGGIOLO, HEINE ELENA
The general objective of this research was to analyze the challenges of social management in the area of ​​comprehensive community health (ASIC), theoretically based on the authors: Mokate and Saavedra (2008) and Kliksberg (2013), among others. The methodology used adheres to the quantitative paradigm, with a type of descriptive research, non-experimental, transectional, field design. Having as population the Comprehensive Community Health Area (ASIC) of the Miranda Municipality, in the State of Zulia, Venezuela; made up of fifty-four doctors distributed in the ASICs of Las Salinas and Alto Viento. The survey technique was used, with a questionnaire-type instrument with thirty-nine items, Likert-type scale, validated by five experts, reaching a reliability of 0.92. Descriptive statistics were applied, from whose analysis and discussion a moderate application of the challenges of social management was found, giving priority to the scope of management and technical problems vs. the adaptive ones.